Gene expression changes in uterine myomas in response to ulipristal acetate treatment. Issue 2 (August 2018) - Courtoy, Guillaume E.; Donnez, Jacques; Ambroise, Jérôme; Arriagada, Pablo; Luyckx, Mathieu; Marbaix, Etienne; Dolmans, Marie-Madeleine
Abstract: Research question: Does ulipristal acetate (UPA) modify the expression of genes related to apoptosis or the extracellular matrix in uterine myomas and are any modifications associated with a clinical response? Design: Targeted analysis of 176 apoptosis- or extracellular-matrix-related genes was conducted using polymerase chain reaction (PCR) arrays. Relevant results were validated by quantitative PCR. Four groups were established: responsive short-term (one course, n = 9), responsive long-term (two to four courses, n = 9), non-responsive ( n = 9), and the control group who was not given any hormone therapy ( n = 9). The clinical response was monitored by medical imagery and considered significant when volume reduction was greater than 25%. Results: Compared with untreated myomas, significant changes in expression of four genes were found in UPA-treated myomas. Gene expression of integrin subunit beta 4 was repressed by UPA treatment (fold change [FC] = −12.50, P < 0.001, q < 0.001), tenascin-C expression was downregulated in UPA-responsive patients (FC = −2.50, P = 0.010, q = 0.090), survivin was repressed in short-term UPA-responsive tumours (FC = −7.69, P < 0.001, q = 0.010), and catenin delta 2 gene expression was upregulated in non-responsive myomas (FC = +7.36, P < 0.001, q = 0.010). Conclusion: This characterization provides the first molecular distinction between myomas responsive or non-responsive to UPA treatment.